Accounting for strain variations and resistance mutations in the characterization of hepatitis C NS3 protease inhibitors. (December 2014) - Ehrenberg, Angelica E.; Schmuck, Benjamin; Anwar, Muhammad Ikram; Gustafsson, Sofia Svahn; Stenberg, Gun; Danielson, U. Helena
Abstract Context: Natural strain variation and rapid resistance development makes development of broad spectrum hepatitis C virus (HCV) drugs very challenging and evaluation of inhibitor selectivity and resistance must account for differences in the catalytic properties of enzyme variants. Objective: To understand how to study selectivity and relationships between efficacy and genotype or resistant mutants for NS3 protease inhibitors. Materials and methods: The catalytic properties of NS3 protease from genotypes 1a, 1b and 3a, and their sensitivities to four structurally and mechanistically different NS3 protease inhibitors have been analysed under different experimental conditions. Results: The optimisation of buffer conditions for each protease variant enabled the comparison of their catalytic properties and sensitivities to the inhibitors. All inhibitors were most effective against genotype 1a protease, with VX-950 having the broadest selectivity. Discussion and conclusion: A new strategy for evaluation of inhibitors relevant for the discovery of broad spectrum HCV drugs was established.